A 1.5V 3bit, 500MS/s LOW POWER CMOS Flash ADC (International Journal of Engineering and Computer Science, 2014)
The analog to digital converters play a vital role in today’s world of electronic systems. The requirement of present applications demands is high speed and low power analog to digital converter. Out of the available ADCs Flash ADC is most popular for its highest conversion rate and its wide applications. In this paper, a 1.5v, 3-bit 500MS/s CMOS flash ADC is presented in 0.180 μm. Improved calibration capabilities resulted in an INL and DNL smaller than 0.20 LSB with power dissipation of 2.48mw.Flash ADC has major components like comparators, thermometer to binary encoder. The comparators are replaced by op-amp. A novel architecture is designed for thermometer to binary encoder by using Full adders. The applications of flash ADC include data acquisition, satellite communication, radar processing, sampling oscilloscopes, and high-density disk drives